Anti‐glypican‐1 antibody‐drug conjugate exhibits potent preclinical antitumor activity against glypican‐1 positive uterine cervical cancer. Issue 5 (31st October 2017) - Matsuzaki, Satoko; Serada, Satoshi; Hiramatsu, Kosuke; Nojima, Satoshi; Matsuzaki, Shinya; Ueda, Yutaka; Ohkawara, Tomoharu; Mabuchi, Seiji; Fujimoto, Minoru; Morii, Eiichi; Yoshino, Kiyoshi; Kimura, Tadashi; et al.
Abstract : Glypican‐1 (GPC1) is highly expressed in solid tumors, especially squamous cell carcinomas (SCCs), and is thought to be associated with disease progression. We explored the use of a GPC1‐targeted antibody‐drug conjugate (ADC) as a novel treatment for uterine cervical cancer. On immunohistochemical staining, high expression levels of GPC1 were detected in about 50% of uterine cervical cancer tissues and also in a tumor that had relapsed after chemoradiotherapy. Novel anti‐GPC1 monoclonal antibodies were developed, and clone 01a033 was selected as the best antibody for targeted delivery of the cytotoxic agent monomethyl auristatin F (MMAF) into GPC1‐positive cells. The anti‐GPC1 antibody was conjugated with MMAF. On flow cytometry, HeLa and ME180 cervical cancer cells highly expressed GPC1, however, RMG‐I ovarian clear cell cancer cell line showed weak expression. The GPC1‐ADC was rapidly internalized into GPC1‐expressing cells in vitro and was potently cytotoxic to cancer cells highly expressing GPC1. There were no inhibitory effects on cancer cells with low expression of GPC1. In a murine xenograft model, GPC1‐ADC also had significant and potent tumor growth inhibition. GPC1‐ADC–mediated G2/M phase cell cycle arrest was detected, indicating that the dominant antitumor effect in vivo was MMAF‐mediated. The toxicity of GPC‐ADC was tolerable within the therapeutic dose range in mice. Our data showed that GPC1‐ADC has potential as a promising therapy for uterine cervical cancer. Abstract : What's new? Antibody‐drug conjugates (ADC) are potent targeted treatments for various cancers, but their potential for cervical cancer remains little explored. After showing that Glypican‐1 (GPC1) is highly expressed in cervical cancer, the authors developed a novel anti‐GPC1 monoclonal antibody with cell internalization activity to produce an ADC linked to the cytotoxic agent monomethyl auristatin F. The ADC potently inhibited the growth of GPC1‐positive cervical cancer cells in vitro and in vivo . Because GPC1 expression levels in normal tissues are lower than in cancer cells, targeting GPC1 with an ADC could be an attractive therapeutic approach for cervical and other GPC1‐expressing tumors.